2011
DOI: 10.1007/s11357-010-9201-5
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, but not dihydroresveratrol, induces premature senescence in primary human fibroblasts

Abstract: Resveratrol, trans-3,5,4'-trihydroxystilbene, is a polyphenolic compound which has been reported to mimic the gene expression patterns seen in whole animals undergoing dietary restriction. The mechanism of action of resveratrol remains poorly understood, but modulation of both cellular proliferation and apoptosis has been proposed as important routes by which the molecule may exert its effects. This study reports the effects of both resveratrol and dihydroresveratrol (a primary in vivo metabolite) on the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Data acquired with our dual purpose real-time cell analyzer (RTCA) further highlighted that RSV, RSVT and PTER significantly inhibited the migration of B16F10 cells, while dihydro-RSV, stilbene and RSVN exhibited no similar effect ( Figure 2 E ). The biofunctions of RSV and the analogs have also been studied in other published reports as summarized in Figure 2 F 36 - 46 . As with the published data and our functional experimental testing (Figure 2 F), the RSVN analog shares similar bioactivities with RSV except for the inhibition of cell migration, which indicates that the presence of 4'-hydroxystilbene within the RSV structure is essential for its anti-migration activity.…”
Section: Resultsmentioning
confidence: 99%
“…Data acquired with our dual purpose real-time cell analyzer (RTCA) further highlighted that RSV, RSVT and PTER significantly inhibited the migration of B16F10 cells, while dihydro-RSV, stilbene and RSVN exhibited no similar effect ( Figure 2 E ). The biofunctions of RSV and the analogs have also been studied in other published reports as summarized in Figure 2 F 36 - 46 . As with the published data and our functional experimental testing (Figure 2 F), the RSVN analog shares similar bioactivities with RSV except for the inhibition of cell migration, which indicates that the presence of 4'-hydroxystilbene within the RSV structure is essential for its anti-migration activity.…”
Section: Resultsmentioning
confidence: 99%
“…Previously Demidenko and Blagosklonny also analysed the effects of resveratrol on human embryonic lung fibroblasts WI-38 and found that resveratrol prevents senescence but this was rather at high, near-toxic concentrations [ 29 ]. On the other hand Faragher et al [ 30 ] showed that above 25μM resveratrol concentrations produces a dose dependent reduction in proliferation of human foetal lung fibroblasts associated with increased SA-β-gal activity. In general, our data are in line with these reports; the only slight difference is that in BJ (foreskin) fibroblasts as low as 10 μM of resveratrol can induce senescence whereas 100μM or over induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (Sigma Aldrich, UK; 1 ) was used to synthesise dihydroresveratrol 2 as reported previously [ 47 ]. ( E )-N-(4-(3,5-Dimethoxystyryl)phenyl) methanesulfonamide 3 was synthesised from the previously reported nitro-substituted analogue 7 via an Fe/NH 4 Cl reduction to give amine 8 [ 26 ], followed by sulfonylation with methanesulfonyl chloride (Fig.…”
Section: Methodsmentioning
confidence: 99%